Management of Femoral Shaft Fracture in Klippel-Trenaunay Syndrome with External Fixator. (17th January 2016) - Gupta, Yogendra; Jha, Ranjib Kumar; Karn, Navin Kumar; Sah, Sanjaya Kumar; Mishra, Bibhuti Nath; Bhattarai, Manoj Kumar
Abstract : Klippel-Trenaunay syndrome (KTS) is a rare complex malformation characterized by the clinical triad of capillary malformations, soft tissue and bone hypertrophy, and venous/lymphatic malformation. Fractures of long bones in such cases are challenging to treat. A 12-year-old female with this syndrome presented with femoral shaft fracture of right thigh. She was initially kept on skeletal traction for two weeks and then she underwent closed reduction and immobilization with external fixator with uneventful intraoperative and postoperative period. Fracture united at four and half months.